2018
DOI: 10.1371/journal.pone.0197411
|View full text |Cite
|
Sign up to set email alerts
|

A study on plant root apex morphology as a model for soft robots moving in soil

Abstract: Plants use many strategies to move efficiently in soil, such as growth from the tip, tropic movements, and morphological changes. In this paper, we propose a method to translate morphological features of Zea mays roots into a new design of soft robots that will be able to move in soil. The method relies on image processing and curve fitting techniques to extract the profile of Z. mays primary root. We implemented an analytic translation of the root profile in a 3D model (CAD) to fabricate root-like probes by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Three-dimensional root tip shapes have been previously shown to affect the penetration ability of roots into soil in wheat ( Colombi et al, 2017 ), or into a hard medium in Arabidopsis ( Roue et al, 2020 ). In addition, an engineering approach using soft robots suggested that plant root tip morphology governs the penetration stress and the efficient elongation in soil ( Mishra et al, 2018 ). Our simulations indicated that the mechanical force produced by the tissue growth was uniformly distributed on the surface of the catenary-curved root tips ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional root tip shapes have been previously shown to affect the penetration ability of roots into soil in wheat ( Colombi et al, 2017 ), or into a hard medium in Arabidopsis ( Roue et al, 2020 ). In addition, an engineering approach using soft robots suggested that plant root tip morphology governs the penetration stress and the efficient elongation in soil ( Mishra et al, 2018 ). Our simulations indicated that the mechanical force produced by the tissue growth was uniformly distributed on the surface of the catenary-curved root tips ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The stress transfer and pore water distribution, however, are nearly impossible to obtain experimentally. Meanwhile, there is an increasing need to fundamentally understand how roots grow, displace, and stabilize between soil particles, largely motivated by a growing interest in bio-inspired robotics [55,56]. With particle-scale modeling techniques, such as the discrete element method (DEM), mechanical interactions between particles and root branches can be simulated explicitly.…”
Section: -4mentioning
confidence: 99%
“…Further developments led to PLANTOIDS, robotic systems inspired by plant roots for soil exploration and monitoring [128]. In this field, other examples are works by Tonazzini et al [130] nd Mishra et al [131] for the study and development of robotic probes with root-like morphologies able to better accomplish penetration tasks. In particular, the latter working group developed an artificial root-like shaped probe inspired by Zea mays roots using 3D printing technology, which is more efficient in terms of penetration force and energy consumption compared to standard shape probes [131].…”
Section: Tropic Nastic and Other Movementsmentioning
confidence: 99%